Telomere maintenance and DNA damage responses during lung carcinogenesis - Lantuejoul, Sylvie; Raynaud, Christophe; Salameire, Dimitri; Gazzeri, Sylvie; Moro-Sibilot, Denis; Soria, Jean-Charles; Brambilla, Christian; Brambilla, Elizabeth (Clinical cancer research, 2010)
Telomere shortening is an early event in bronchial carcinogenesis, preceding P53/Rb pathway inactivation and telomerase reactivation, and leading to DNA damage responses (DDR). As their inactivation in cancer increases genetic instability, our objective was to identify the chronology of telomere machinery critical events for malignant progression. We have evaluated telomere length by fluorescence in situ hybridization and analyzed DDR proteins p-CHK2, p-ATM, and p-H2AX, and telomeric maintenance proteins TRF1 and TRF2 expression by immunohistochemistry in normal bronchial/bronchiolar epithelium, and in 109 bronchial preneoplastic lesions, in comparison with 32 squamous invasive carcinoma (SCC), and in 27 atypical alveolar hyperplasia (AAH) in comparison with 6 adenocarcinoma in situ (AIS; formerly bronchiolo-alveolar carcinoma) and 24 invasive adenocarcinoma (ADC). Telomere length critically shortened at bronchial metaplasia stage to increase gradually from dysplasia to invasive SCC; in bronchiolo-alveolar lesions, telomere length decreased from normal to AIS and increased from stage I to II to stage III to IV ADC. Expression of TRF1 and TRF2 increased progressively from dysplasia to SCC and from AAH to invasive ADC. The expression of concomitant DDR proteins increased significantly from low- to high-grade dysplasia and from AAH to AIS and stage I to II ADC. P-CHK2 and p-H2AX expressions were highly correlated and both decreased, along with p-ATM, in SCC and advanced ADC. Telomere attrition occurs at the earliest stage of lung carcinogenesis as an initiating event, preceding TRF1 and TRF2 overexpression for telomere stabilization. In contrast, dismiss of DDR, through p-H2AX and p-CHK2 downregulation, represents a late progressing event associated with SCC and ADC progression.